South East Europe Regular Economic Report, June 2012 - World Bank (Washington, DC, 2012)
After they achieved 2.2 percent growth in 2011, early indications are that the economies of the six countries in South East Europe (the SEE6: Albania, Bosnia and Herzegovina (BIH), Kosovo, FYR Macedonia, Montenegro, and Serbia) are slowing drastically and can expect just 1.1 percent growth in 2012. Economic conditions in the Euro zone are holding back economic activity and depressing government revenues in SEE6 countries. With both public debt and financing pressures high, most countries in the region need to embark on major fiscal consolidation programs if they are to reverse their adverse debt dynamics and avoid financing problems down the road. The good news is that in general the SEE6 financial sectors are still relatively well placed, despite elevated risks and vulnerability to adverse shocks, especially the possibility of contagion if the Greek crisis should intensify. The bad news is social: SEE6 countries have the highest unemployment and poverty rates in Europe. Yet even with the difficult short-term situation, SEE6 countries now have historic opportunity to board the European 'convergence train' and over the long term reduce their per capita income gap with developed European Union (EU) countries. All earlier entrants were able to 'catch up quickly.' In principle, the same 'convergence train' is now pulling into the EU candidate countries in SEE6; but these gains are not automatic, they will materialize only if country policies and reforms facilitate them. The long-term SEE6 structural reform agenda must leverage greater trade and financial integration and reform labor markets and the public sector.